How national models of solidarity shaped public support for policy responses to the COVID-19 crisis in 2020–2021 - Goerres, Achim; Vail, Mark I. (Frontiers in Political Science, 2024)
How do national models of solidarity shape public support for distinctive policy responses to social and economic crises, such as the COVID-19 pandemic? We analyze American and German policy responses from March 2020 to June 2021 across a number of economic and social policy domains and identify path-dependent institutional contingencies in both countries despite the same crisis experience. Drawing from ten different sources of public opinion data, we then triangulate the pandemic's effects on public support for individualized and collectively oriented policy responses. Aside from emotional rally-to-the-flag effects, the policy-specific public reactions are consistent with institutional and normative predicates of the two political economies: the German public seems to be supportive of aggressive policies to combat inequality, though in ways that privilege established social collectivities and groups, whereas in the US, we only see moderate evidence of support for time-limited and individually-focused measures designed to remain in place only for the duration of the crisis.